2017
DOI: 10.1111/gcb.13767
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic carbon dynamics jointly controlled by climate, carbon inputs, soil properties and soil carbon fractions

Abstract: Soil organic carbon (SOC) dynamics are regulated by the complex interplay of climatic, edaphic and biotic conditions. However, the interrelation of SOC and these drivers and their potential connection networks are rarely assessed quantitatively. Using observations of SOC dynamics with detailed soil properties from 90 field trials at 28 sites under different agroecosystems across the Australian cropping regions, we investigated the direct and indirect effects of climate, soil properties, carbon (C) inputs and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
157
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 375 publications
(186 citation statements)
references
References 66 publications
7
157
2
1
Order By: Relevance
“…In a recent paper, Luo, Feng, Luo, Baldock, and Wang () demonstrate that SOC dynamics in agricultural systems are mainly driven by, in order of importance, the amount and quality of C inputs to the soil from plant residues, climate, and soil properties including the amount and composition of soil C. While we concur with Luo et al. () that the average C input amount is the most influential variable on SOC change rate, their experimental set‐up did not enable its weight to be accurately quantified. They apply a path analysis and make use of an extensive data set that comprises detailed soil properties from 90 Australian field trials.…”
contrasting
confidence: 50%
See 3 more Smart Citations
“…In a recent paper, Luo, Feng, Luo, Baldock, and Wang () demonstrate that SOC dynamics in agricultural systems are mainly driven by, in order of importance, the amount and quality of C inputs to the soil from plant residues, climate, and soil properties including the amount and composition of soil C. While we concur with Luo et al. () that the average C input amount is the most influential variable on SOC change rate, their experimental set‐up did not enable its weight to be accurately quantified. They apply a path analysis and make use of an extensive data set that comprises detailed soil properties from 90 Australian field trials.…”
contrasting
confidence: 50%
“…According to these data, the assumptions proposed would fit to potatoes, while Luo et al. () consider winter wheat and pasture. In addition, root‐derived C inputs are likely to contribute massively to soil C built‐up as they are more persistent in soil on a decadal time scale than inputs from aboveground tissue (Kätterer et al., ; Rasse, Rumpel, & Dignac, ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with previous findings that climate exerts dominant controls on SOM decomposition (Carvalhais et al., 2014; Kirschbaum, 2004; Sun et al., 2004). A recent synthesis by Luo, Feng, Luo, Baldock, and Wang (2017) showed that climate (precipitation and temperature) accounted for as much as 25% of the relative influence on SOC by various environmental, soil biotic, and abiotic factors. Within given temperatures, however, we found that soil substrate had much greater influence on the rate of soil C mineralization than microbial inoculum, suggesting the importance of soil quality in determining the soil C mineralization—possibly the microbial adaptation to the soil matrix.…”
Section: Discussionmentioning
confidence: 99%